Work-life balance and job satisfaction of shipyard industry employees in Surabaya - Shani Agung Nugroho; Indriati Paskarini; Xindy Imey Pratiwi (International Journal of Public Health Science (IJPHS), 2023)
Job satisfaction is a contented feeling of employees when they are able to fulfill expectations for needs with good work-life balance conditions so that they can work effectively and efficiently. The goal of this study was to find out how workers in the shipyard industry feel about their work-life balance and how happy they are with their jobs. The variables were the characteristics of employees (age, education level, marital status, and years of service). The data were shown in frequency distribution tables and cross tabulations. Chi-square test was employed to analyze the data. The work-life balance of employees was related to their age (sig. 0.039), but not to their level of education (sig. 0.723), marital status (sig. 0.535), or number of years of service (sig. 0.724). The results of statistical tests on the two main factors showed that work-life balance and job satisfaction were linked (sig. 0.019). Overall, employees in the shipyard industry were much happier with their jobs when they had a good balance between work and life. The company is expected to maintain the work-life balance of its employees to increase the job satisfaction of the workers and indirectly increase the achievement of work productivity in the company.